Lameness in UK dairy cows: a review of the current status - Archer, Simon C.; Bell, Nick; Huxley, Jonathan (BMJ, 2010)
Lameness in dairy cattle has been reported as a concern for welfare and economic reasons for over 20 years. This concern has been expressed from across the industry and has prompted the launch of a number of initiatives to address the problem. This article reviews the current status of lameness in dairy cows in the UK, outlines the current understanding of the condition and its impacts on welfare and productivity, and highlights areas where evidence is still lacking.